Possible algorithms for determining adverse reactions caused by food supplements in Romania - Irina Mihaela MATRAN (Asociatia de Biosiguranta si Biosecuritate, 2021)
Introduction. The advertising of food supplements on various media channels or in specialty stores with natural products and other places, as well as the lack of informative and educational programs for the population upon side effects and the interaction of food supplements with food and drugs, have led to the development of uncontrolled marketing of these products.